Men in civilian dress with dogs at U. S Army barracks at Nome, Alaska, between 1898 and 1900 - Hester, Wilhelm, 1872-1947 (1898)
PH Coll 318.1072 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number